2004
DOI: 10.1016/j.tplants.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Auxin signaling and regulated protein degradation

Abstract: Auxin regulates many aspects of plant growth and development. Auxin is known to regulate gene expression through degradation of the AUX/IAA proteins, short-lived nuclear proteins that regulate gene transcription. The AUX/IAA proteins are degraded through the action of a ubiquitin protein ligase called SCF TIR1 . Auxin promotes the interaction between AUX/IAA proteins and SCF TIR1 in a soluble extract, suggesting that the auxin receptor is a soluble factor. These studies also indicate that the auxin-induced AUX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
143
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(152 citation statements)
references
References 58 publications
3
143
0
6
Order By: Relevance
“…Biochemical and genetic studies have shown that IAA7/AXR2 and IAA17/AXR3 proteins are targeted for ubiquitinmediated proteolysis by the SCF TIR1 ubiquitin ligase complex. The interactions of IAA7/AXR2 and IAA17/AXR3 proteins with the SCF TIR1 complex involve domain II and occur in an auxindependent manner (Gray et al, 2001;Dharmasiri et al, 2003;Dharmasiri and Estelle, 2004;Kepinski and Leyser, 2004). Auxin directly binds to the TRANSPORT INHIBITOR RESPONSE1/ AUXIN RECEPTOR F-BOX (TIR1/AFB) proteins, resulting in the degradation of the Aux/IAA proteins (Dharmasiri et al, 2005a(Dharmasiri et al, , 2005bKepinski and Leyser, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and genetic studies have shown that IAA7/AXR2 and IAA17/AXR3 proteins are targeted for ubiquitinmediated proteolysis by the SCF TIR1 ubiquitin ligase complex. The interactions of IAA7/AXR2 and IAA17/AXR3 proteins with the SCF TIR1 complex involve domain II and occur in an auxindependent manner (Gray et al, 2001;Dharmasiri et al, 2003;Dharmasiri and Estelle, 2004;Kepinski and Leyser, 2004). Auxin directly binds to the TRANSPORT INHIBITOR RESPONSE1/ AUXIN RECEPTOR F-BOX (TIR1/AFB) proteins, resulting in the degradation of the Aux/IAA proteins (Dharmasiri et al, 2005a(Dharmasiri et al, , 2005bKepinski and Leyser, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, extensive genetic and biochemical studies in Arabidopsis reveal that auxin signalling is mediated by a cascade that regulates the proteasomal degradation of the Auxin/INDOLE ACETIC ACID (Aux/IAA) transcriptional repressors in an auxin-dependent manner [1][2][3] . When the intracellular concentration of auxin is low, Aux/IAAs directly interact with AUXIN RESPONSE FACTORS (ARFs), a class of transcription factors that control the expression of downstream auxin-responsive genes, and thereby inhibit the transcriptional activity of ARFs.…”
mentioning
confidence: 99%
“…This miRNA is predicted to target the F-box protein TIR1, which functions as a regulator of auxin signaling through its role in targeting Aux/IAA proteins for degradation via the ubiquitin/ proteasome pathway. Aux/IAA proteins repress the activity of auxin response factors and may function as negative or positive regulators of gene transcription (Dharmasiri and Estelle, 2004). Abiotic stress induction of miRNA393 could impose another level of regulation on TIR1-mediated responses.…”
mentioning
confidence: 99%